Pengaruh Pemberian Berbagai Macam Kompos pada Lahan Ultisol terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays Saccharata Sturt) (Jurnal Agro Teknologi Tropika, 2012)
Sweet corn has a high nutrient content, have a good taste for the public, so that demand is rising but it is notaccompanied by an increase in production, so that there is insufficient supply of sweet corn. Compost is one of organicfertilizer derived from the rest waste of animal or plant. Ultisol soil has relatively low acidity levels, dosages of fertilizer, andthe availability of organic matter and other obstacles in agriculture. One way to overcome this problem is by composting.The purpose of this research was to determine the effect of good compost from the growth and production of sweet corn.This research has been completed in the site of Faculty of Agriculture, University of Riau using a Complete RandomizedDesign with 6 treatments and 4 replications. The further test has conducted using DNMRT 5%. The result showed that amixture of compost and stover rice straw rice straw compost will provide a high return on investment of growth andproduction of sweet corn.Keyword : sweet corn, ultisol soil, compost